Pengaruh Komitmen Organisasi, Pengetahuan Whistleblowing, Sikap, dan Personal Cost Terhadap Minat Melakukan Whistleblowing Pada Bank BNI 46 Wilayah 9 Banjarmasin - Hidayat, Erwan (Universitas Darwan Ali, 2025)
Whistleblowing is one of the media to obtain information from within the company to find out if there is fraud or unethical actions in the company. This study aims to determine the interest in conducting whistleblowing by employees as seen from the variables of organizational commitment, whistleblowing knowledge, attitude and personal cost. This study uses quantitative methods using primary data sources. The data collection technique used a questionnaire distributed to employees of the BNI Regional Office 9 Banjarmasin. The sample used in the study was 140 respondents including employees of the BNI Regional Office 9 Banjarmasin. The results of the study show that organizational commitment and whistleblowing knowledge do not influence the interest in conducting whistleblowing. Meanwhile, personal costs have a positive influence on the interest in conducting whistleblowing and attitude variables have a negative influence on the interest in conducting whistleblowing.